2013
DOI: 10.2489/jswc.68.6.450
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phosphorus retention in irrigation laterals

Abstract: Irrigation laterals transport irrigation return flow, including water, sediment, and dissolved nutrients, such as phosphorus (P), back to surface water bodies. Phosphorus transformations during transport can affect both P bioavailability and the best management practices selected to minimize P inputs to waters of the United States. The objective of this study was to determine P retention in three irrigation laterals. Soluble reactive P (SRP) concentrations in lateral waters were increased from 0.08 to 0.25 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…In fact, the primary P loss pathway from agricultural soils is through surface runoff (Vadas et al, 2004), which may be enhanced by the use of certain irrigation systems. Furthermore, once in irrigation return flow waters, P may be transported distances greater than 18 km (Ippolito and Nelson, 2013). Thus, managing irrigation practices may help control runoff and consequently reduce P losses from agricultural systems.…”
mentioning
confidence: 99%
“…In fact, the primary P loss pathway from agricultural soils is through surface runoff (Vadas et al, 2004), which may be enhanced by the use of certain irrigation systems. Furthermore, once in irrigation return flow waters, P may be transported distances greater than 18 km (Ippolito and Nelson, 2013). Thus, managing irrigation practices may help control runoff and consequently reduce P losses from agricultural systems.…”
mentioning
confidence: 99%
“…The concentration of DP in furrow irrigation runoff is related to soil test P concentration and the amount of sediment detached by flow in irrigation furrows (Bjorneberg et al, 2006). Research investigating the transformations and transport of DP through the return flow system has suggested that DP in runoff from furrow-irrigated fields likely remains in the water until it returns to the Snake River (Ippolito and Nelson, 2013).…”
Section: Water Quality and Nutrient Loading In The Upper Snake Rock Wmentioning
confidence: 99%